Evaluation the Effectiveness of Nephelium lappaceum (Nl) Peel Aqueous Extract Against Hepatocellular Carcinoma Induced by Thioacetamide (TAA) in Male Albino Rats - Fadel Thabet, Zahraa; A. Abd-Alsalam Alsalame, Heba (Pure Sciences International Journal of Kerbala, 2024)
This study aims to evaluate the effectiveness of Nephelium lappaceum (Nl) peel aqueous extract against liver cancer induced by Thioacetamide (TAA). This study has been conducted in the College of Education for Pure Sciences / University of Karbala and the animal house of Pharmacy College / University of Karbala for the period from the beginning of November 2023 until February 2024 , and the Physiological tests have been done in Al-Husseini Teaching Hospital in the Holy Karbala Governorate / Department of Clinical Chemistry. 40 male rats (12 weeks old , weighing 250 grams) are divided into four groups. First group (G1) is administered distilled water, the second group (G2) is injected 200 mg/kg Thioacetamide (TAA) while the third group (G3) is administered 25mg/kg Nephelium lappaceum (Nl) peel aqueous extract. Fourth group (G4) is administered 25mg/kg Nephelium lappaceum (Nl) peel aqueous extract with 200mg/kg Thioacetamide (TAA). After 90 days, blood samples are collected to study the following parameters: alkaline phosphatase (ALP), aminotransaminase transfer (ALT), aspartate transaminase (AST) and total bilirubin (TB) in addition to investigate the histological changes. The results show that TAA causes a significant increase (P < 0.01) in ALT, AST, ALP and T–BIL in (G2) compared with the (G1). While there is no significant increase (P > 0.01) in ALP, ALT, AST and T -BIL in G3 and G4 compared with the control. The results of the histological examination in G2 group reveal that treatment with TAA for 90 days leads to many noxious effects on liver cells with the appearance of many tumor nodules, vacillation and necrosis with infiltration of inflammatory cells. The study concludes that peel aqueous extract of Nephelium lappaceum (Nl) has a protective role against liver cancer induced by TAA in male rats.